Pendampingan Sertifikasi Sistem Verifikasi Legalitas Kayu (SVLK) di PT Devonshire Indotama dalam Meningkatkan Akses ke Pasar Internasional - Sunardiansyah, Yogi Akbar; Ma'rifah, Julia Dewi; Prasetya, Juliasari; Sabila, Maharsi Anis (Jurnal PKM Manajemen Bisnis, 2025)
There are lot of cases of illegal logging and illegal trading related to woods trade in the international market require that wood producers to have proof of woods legality. Since 2009, the Indonesian government has implemented the Woods Legality Verification System (SVLK) with the aim of ensuring that woods or wood products traded come from legal sources. In 2022, the level of SVLK implementation is still considered low due to relatively rapid changes in SVLK policies. In large-scale industries, the implementation of the SVLK system has made quite good progress, in contrast to small-scale industries which have various obstacles including 1) Incomplete company legality documents; (2) Incomplete production process documentation; (3) Expensive SVLK certification costs; (4) There is no improvement in the selling price of SVLK-certified woods; (5) Not all destination countries for woods product exports require SVLK certification; (6) Government policies related to SVLK often change. The mentoring program for Wood Legality Verification System (SVLK) participants is an initiative intended to assist and guide business actors in the wood industry to obtain SVLK certification. SVLK certification is an important prerequisite for entering the global market, especially the European market which applies strict regulations regarding wood imports. By obtaining assistance, business actors can more easily meet these requirements and increase their access to the international market. In addition, through the industrial empowerment assistance program, it can increase the capacity of small industries to comply with applicable forestry regulations. From the results of the assistance that has been carried out, PT Devonshire Indotama has successfully obtained SVLK certification from the Certification Institution appointed by the Ministry of Environment and Forestry.